CRISPR/Cas9-induced knockout reveals the role of ABCB1 in the response to temozolomide, carmustine and lomustine in glioblastoma multiforme. (November 2022) - Radtke, Lena; Majchrzak-Celińska, Aleksandra; Awortwe, Charles; Vater, Inga; Nagel, Inga; Sebens, Susanne; Cascorbi, Ingolf; Kaehler, Meike
Abstract: Glioblastoma multiforme (GBM) is the most common malignant brain tumor with limited therapeutic options. Besides surgery, chemotherapy using temozolomide, carmustine or lomustine is the main pillar of therapy. However, therapy success is limited and prognosis still is very poor. One restraining factor is drug resistance caused by drug transporters of the ATP-binding cassette family, e.g. ABCB1 and ABCG2, located at the blood-brain barrier and on tumor cells. The active efflux of xenobiotics including drugs, e.g. temozolomide, leads to low intracellular drug concentrations and subsequently insufficient anti-tumor effects. Nevertheless, the role of efflux transporters in GBM is controversially discussed. In the present study, we analyzed the role of ABCB1 and ABCG2 in GBM cells showing that ABCB1, but marginally ABCG2, is relevant. Applying a CRISPR/Cas9-derived ABCB1 knockout, the response to temozolomide was significantly augmented demonstrated by decreased cell number (p < 0.001) and proliferation rate (p = 0.04), while apoptosis was increased (p = 0.04). For carmustine, a decrease of cells in G1-phase was detected pointing to cell cycle arrest in the ABCB1 knockout (p = 0.006). For lomustine, however, loss of ABCB1 did not alter the response to the treatment. Overall, this study shows that ABCB1 is involved in the active transport of temozolomide out of the tumor cells diminishing the response to temozolomide. Interestingly, loss of ABCB1 also affected the response to the lipophilic drug carmustine. These findings show that ABCB1 is not only relevant at the blood-brain barrier, but also in the tumor cells diminishing success of chemotherapy. Graphical Abstract: ga1 Highlights: The drug efflux transporter ABCB1, but not ABCG2, is of high relevance in chemoresistance of glioblastoma multiforme cells. CRISPR/Cas9-derived knockout of ABCB1 significantly improves the response to temozolomide in a GBM cell model. Cell cycle arrest after exposure to carmustine, but not to lomustine, is augmented by functional knockout of ABCB1 . ABCB1 is not only important at the blood-brain-barrier, but also at the blood-tumor barrier.